Gender equity and information technology in education: The second decade - Volman, Monique; Eck, Edith van (Review of educational research, 2001)
First, the rapid development in the use of information and communication technology (ICT) in education is outlined. Then the topics of access to computers, computer-related learning processes, and educational outcomes are discussed. The review also provides insight into the background of gender differences in participation in computer activities and performance in relation to ICT. The research reviewed focuses on the role of teachers and fellow classmates, on the different approaches of girls and boys to ICT, and on the preferences of girls regarding the structure and design of software. The research also analyzed the complex meaning of computer attitudes as both a cause and a consequence of differences in the participation and performance of girls and boys. The extent and nature of these differences vary from application to application. (DIPF/Orig.)